PELATIHAN MICROSOFT OFFICE SPECIALIST (MOS) POWER POINT SEBAGAI MEDIA PEMBELAJARAN UNTUK GURU SMKN 1 CISARUA DALAM ERA INDUSTRI 4.0 - Mariya Al Qibtiya; Dadang Lukman Hakim; Bambang Trisno; Budi Mulyanti; Yadi Mulyadi; Tuti Suartini; Elih Mulyana; Wawan Purnama; Aip Saripudin; Silmi At Thahirah Al Azhima; Roer Eka Pawinanto; Nurhidayatulloh Nurhidayatulloh (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
The era of industrial disruption has had many influences on human life, this has also affected the world of education. One way to improve teacher competence in the industrial revolution 4.0 era is to equip teachers with global scale capabilities, namely Microsoft Office Specialists or MOS. From these problems, our training took the initiative to hold Microsoft Office Specialist (MOS) Power Point Activities for vocational/high school teachers in the city of Bandung. This training adapts the Goad training model, namely this model consists of several cycles including: (1) training needs analysis; (2) training approach design; (3) development of training materials; (4) implementation of training; (5) evaluation and updating of training.